(untitled) (International Journal of Environmental Sciences, 2025)
Nowadays, most information is handled online, leaving it open to cyber threats. Cybercrime has seriously harmed people, businesses, and even the government. In the modern world, cybercrime is becoming a very severe concern.A variety of laws and procedures have been put in place to prevent it, and those who engage in cybercrime are subject to sanctions. Our lives are made better by the internet, but there are also some drawbacks. Cybercriminals are always looking for novel methods to target active online victims. Everybody uses computers nowadays, regardless of age. An accurate understanding of cybercriminals’ behavior and the impact they have on people from different socioeconomic strata is necessary to prevent cybercrimes. Therefore, this study publication offers insight into cybercrimes, their impacts on society, and victims of cybercrime. Additionally, it examines the effects of several online safety measures.